Infliximab Preferentially Induces Clinical Remission and Mucosal Healing in Short Course Crohn’s Disease with Luminal Lesions through Balancing Abnormal Immune Response in Gut Mucosa - Lijuan Yu; Xuehua Yang; Lu Xia; Jie Zhong; Wensong Ge; Jianxin Wu; Hongchun Liu; Fei Liu; Zhanju Liu (Mediators of Inflammation)
This study was undertaken to evaluate the efficacy of infliximab (IFX) in treatment of Crohn’s disease (CD) patients. 106 CD patients were undergoing treatment with IFX from five hospitals in Shanghai, China. Clinical remission to IFX induction therapy was defined as Crohn’s disease activity index (CDAI) < 150. Clinical response was assessed by a decrease in CDAI ≥ 70, and the failure as a CDAI was not significantly changed or increased. Ten weeks after therapy, 61 (57.5%) patients achieved clinical remission, 17 (16.0%) had clinical response, and the remaining 28 (26.4%) were failed. In remission group, significant changes were observed in CDAI, the Simple Endoscopic Score for Crohn’s Disease (SES-CD), and serum indexes. Patients with short disease duration (22.2 ± 23.2 months) and luminal lesions showed better effects compared to those with long disease duration (71.0 ± 58.2 months) or stricturing and penetrating lesions. IFX markedly downregulated Th1/Th17-mediated immune response but promoted IL-25 production in intestinal mucosa from remission group. No serious adverse events occurred to terminate treatment. Taken together, our studies demonstrated that IFX is efficacious and safe in inducing clinical remission, promoting mucosal healing, and downregulating Th1/Th17-mediated immune response in short course CD patients with luminal lesions.